LIFE STRUGGLE AS REFLECTED IN RALSTON’S BETWEEN A ROCK AND A HARD PLACE - Geraldus I. Bataha; Tini Mogea; Imelda Lolowang (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The purpose of this study is to reveal about struggle in Ralston’s Between a Rock and a Hard Place. The writers choose qualitative research to be design in this research. Because “qualitative research is descriptive, “The data collected in form of words or picture rather than numbers.” In analyzing the data, the writer used objective approach because the data are take only from the work itself and to see the interrelationship between the elements of the novel. The result shows that adventure of Ralston’s near-death experience while hiking alone in Utah’s Blue John Canyon and the lengths he took to survive Ralston setting of his adventures in the American West and His goal is to bike, climb, and hike his way over a thirty-mile terrain within one day, a boulder he is climbing becomes loose and he falls into the canyon. The boulder pins his right hand and wrist against the wall. Ralston quickly assesses his situation and understands the likelihood that he will die trapped in this canyon.The only real way he can escape is by cutting off his right arm. During his second day in the canyon, he realizes that his dead hand trapped behind the boulder will likely release toxins that will poison him if he isn’t first killed by dehydration, hypothermia, or a flash flood. He tries again to dislodge the boulder using other techniques but makes little progress.